Prohibition of "Uncertainty" in Islam: the case of Virtual Currency - Muhammad Nouman Asghar; Dr. A. Khalid Madni (jihat-ul-islam, 2021)
While Virtual Currency became people’s new form of asset in recent times based on network that is distributed across a large number of computers, it is important to figure out whether it is Sharia compliant or not. Virtual Currency has various characteristics which traditional currency doesn’t have such as its availability only in digital form on computers and mobile phones, hidden identity of buyer and seller during transactions, not issued by any central authority and not controlled by any government or state bank. This decentralized structure of Virtual Currency is completely new and different from other traditional currencies; hence it has to be examined under Islamic Sharia Law. "Gharar" means uncertainty is one of the sins which are prohibited in Islamic Law. The current paper presents the scholarly inquiry about Virtual Currency whether it is comprised of "Gharar" or not.